2022
DOI: 10.3390/plants11202787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Normal Maize Germplasm Collected in South Sudan Revealed by SSR Markers

Abstract: Maize is one of the leading global cereals, and in South Sudan maize cultivation occurs in nearly all of the country’s agro-ecological zones. Despite its widespread cultivation, farmers in South Sudan depend on undeveloped varieties, which results in very low yields in the field. In the current study, 27 simple sequence repeat (SSR) markers were used to investigate genetic diversity and population structures among 37 landrace maize accessions collected from farmers’ fields in South Sudan. In total, 200 alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
3
10
2
Order By: Relevance
“…This result is peculiar to outcrosses, which show a higher degree of variability within populations than among populations [ 53 , 70 ]. The result is consistent with the findings of Nelimor et al [ 71 ], Mathiang et al [ 72 ], Ayesiga et al [ 53 ], and Zawadi et al [ 73 ] who reported 83–97% variability within maize populations. The presence of significantly higher variation within the three subpopulations of the tested inbred lines enables the effective selection of core sets of inbred lines that capture the maximum allelic richness of the respective subpopulations, resulting in the identification of genotypes with desirable traits [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result is peculiar to outcrosses, which show a higher degree of variability within populations than among populations [ 53 , 70 ]. The result is consistent with the findings of Nelimor et al [ 71 ], Mathiang et al [ 72 ], Ayesiga et al [ 53 ], and Zawadi et al [ 73 ] who reported 83–97% variability within maize populations. The presence of significantly higher variation within the three subpopulations of the tested inbred lines enables the effective selection of core sets of inbred lines that capture the maximum allelic richness of the respective subpopulations, resulting in the identification of genotypes with desirable traits [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…These studies investigated the phenotypic traits of maize accessions from Italy, the north-eastern Himalayas, and Algeria respectively and found that the accessions were not clustered together based on their geographical region. Mixing of germplasm accessions among local farms could be the reason behind the weak relationship among the accessions from the same region, which is the same finding that was reported in our previous report for accession clustering based on microsatellite marker data (Mathiang et al 2022).…”
Section: Discussionsupporting
confidence: 87%
“…Utilization of this method will help in forming an accurate estimation of the level of phenotypic variation in maize accessions collected from South Sudan. In a previous study, we used simple sequence repeat (SSR) or microsatellite markers for genetic diversity studies of maize landrace accessions collected from South Sudan, and provided the first report about the genetic variation of maize landrace accessions of South Sudan (Mathiang et al 2022). Recently, many tools have become available for studying the genetic relationships between landrace germplasm using various molecular markers; however, morphological characterization is the first step in germplasm evaluation and classification (Smith et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The length of the burn-in period was set at 10,000, and the number of Markov chain Monte Carlo (MCMC) repeats after burn-in was set at 100,000 to estimate individual admixture proportions ( Q ). Evanno’s method [ 49 ] and the online software Structure Harvester [ 50 ] were used to determine the optimal grouping K values [ 51 , 52 , 53 ]. Principal coordinate analysis (PCoA) was performed using GenAlex 6.41 software [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%